Reduction of coating time for catheter process - Nur Farah Hanum Binti Zakaria (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The coting is the process for covering up to the surface outer of catheter. This study was conducted in order to reduce the time fir coating process in manufacturing cathter by using the process flow method. This study will focus on the process flow that required a long time to coating catheter.